ЕНЕРГЕТИЧНІ ПОКАЗНИКИ ПЕРЕТВОРЮВАЧА ЕНЕРГІЇ МОРСЬКИХ ХВИЛЬ З ВИПРЯМЛЯЧЕМ СТРУМУ ТА АКТИВНО-ЄМНІСНИМ НАВАНТАЖЕННЯМ - Кондратенко, І.П.; Крищук, Р.С. (Інститут електродинаміки Національної академії наук України, 2024)
The article is dedicated to determining the energy indicators of a generating complex with stochastic wave energy generation. The aim of the study is to compare the energy indicators and power consumption coefficient of wave energy generating complexes' simulation models with magneto-electric generators operating at variable speeds under resistive and resistive-capacitive loads with rectified voltage. The analytical method is employed to calculate the parameters and energy indicators of the magneto-electric generator. The calculation includes inductance, resistance, and voltage generated by the rotor with permanent magnets in the three-phase winding of the magneto-electric generator for electrical circuit modeling with and without a three-phase current rectifier, as well as active-reactive and active loading. The rotor rotation frequency varies harmonically with the same period and amplitude for all electrical circuits. The determined current in the electrical circuits is used to calculate the generator's electromagnetic field and energy indicators. Comparisons are made for circuits with active and active-reactive loads, including power consumption, power losses in the stator winding, power output from the generator, and the power consumption coefficient of wave energy. The comparison of energy indicators is conducted under the condition of equal rotor oscillation frequency and shaft torque, achieved by varying the load resistance. Bibl. 10, fig. 8, table.